1029 Anthracycline and trastuzumab-induced subclinical cardiac damage and its prevention in the SAFE trial. Myocardial strain imaging and 3D echo interim analysis data. (17th January 2020) - Barletta, G; Livi, L; Martella, F; Desideri, I; Venditti, F; Scotti, V; Pilato, G; Argiro", A; Becherini, C; Bacci, C; Terziani, F; Visani, L; et al.
Abstract: Background: Benefit of anthracyclines and trastuzumab therapies on disease-free survival in breast cancer is well known. Cardiotoxicity is a feared potential complication of both drugs. It usually progresses from cardiomyocyte injury to silent left ventricular dysfunction (LVD) which often becomes symptomatic and irreversible. Therefore, its prevention and early detection are of paramount importance in these cancer patients. Purpose: SAFE trial (CT registry ID: NCT2236806) is a randomized phase 3, four-arm, single-blind, placebo-controlled study that aims to evaluate the effects of Bisoprolol (B) (5 mg, twice daily), Ramipril (R) (5 mg, twice daily) or the combination of the two (R + B), compared to placebo (P), on subclinical heart heart damage. Interim data of left ventricular function monitored with 3D Echo and Myocardial Strain Imaging are presented. Methods: Out of 225 patients asked to participate, 191 were enrolled (mean age 48.9 ± 9.0 years). Follow-up monitoring (at 3, 6, 12 months[m]) comprised 3D ejection fraction (3D-LVEF) and Global Longitudinal Strain (GLS). One patient had sub-acute anthracyclines cardiotoxicity. Data at one year of 123 patients were available (34 P, 28 R, 31 B, 30 R + B). Results: At time 0, no significant differences in age, body mass index, hemodynamic parameters were observed among arms. Data of 3D-LVEF and GLS at time 0 and during follow-up are reported in the figure (p level versus time 0 – GLS repeated measures). There was a significant reduction in 3D LVEF and increase in GLS in P arm (3D LVEF: 3m: -3.3%, 6m: - 5.2%, 12m: -3.7%; GLS: 3m: +5, 7%, 6m: +7.8%, 12m: + 7, 1%). A similar, though less significant, worsening of 3D LVEF (-2.4%, -1.9%, -2.2% at 3, 6, 12m, respectively) and GLS (+2.7%, +3.2% at 3 and 6m, respectively) was found in R arm. In B and B +R arms there was a worsening at 6m (3D LVEF -2.5%, GLS +2.7%), whereas at 12m only GLS increased (+3.2%) in B, not in B + R. Arm differences were significant (repeated measures two ways) both for 3D LVEF (two-way repeated measures ANOVA, p level = 0.038, observed power 0.855) and GLS (p level = 0.002, observed power 0.973). Conclusions: This interim analysis of the SAFE trial shows that demonstration of subclinical cardiotoxicity is feasible with 3D echo and myocardial strain imaging. Significant subclinical damage potentially leading to LVD is present at one year. Both B alone on in combination with R may be a successful cardioprotective strategy in patients treated with anthracyclines and trastuzumab.